Developmentally induced autolysis during fruiting body formation by Myxococcus xanthus. - Wireman, J W (1977)
The developmental events during fruiting body construction by the myxobacterium M. xanthus is an orderly process characterized by several sequential stages: growth leads to aggregation leads to formation of raised, darkened mounds of cells leads to autolysis leads to myxospore induction. The temporal sequence of autolysis followed by myxospore induction is consistent with the interpretation that developmental autolysis provides essential requirements for the surviving cells to induce to myxospores. At intermediate developmental times on agar plates a fraction of the cell population is irreversibly committed to lyse; i.e., lysis continues in liquid growth medium or in magnesium-phosphate buffer. Lysis is cell concentration independent and is therefore likely to be by an autolytic mechanism. The lysis sequence can be preliminarily characterized as having an early stage during which deoxyribonucleic acid synthesis continues and a later irreversible stage during which deoxyribonucleic acid synthesis does not occur. Irreversible lysis in liquid growth medium or in magnesium-phosphate buffer is initiated on agar plates during nutrient deprivation and such lysis results in the induction of a fraction of the population to myxospores. This induction is dependent upon the concentration of lysis products, thus providing evidence that developmentally induced autolysis is required for myxospore induction.